Experiencing and protecting sacred natural sites of Sámi and other indigenous peoples : the sacred Arctic - Heinämäki, Leena; Herrmann, Thora Martina (Springer, 2017)
This book focuses specifically on the experience and protection of indigenous, and particularly Sámi sacred sites in the Arctic. Sacred sites are being increasingly recognized as important reservoirs of Arctic cultural and biological diversity, as a means for the transmission of culture and identity, and a tool for the preservation of fragile northern social-ecological systems. Yet, legal protection of Arctic sacred sites and related policies are often still lacking or absent. It becomes increasingly difficult for site custodians in the Arctic to protect these ancient sites, due to disruptive changes, such as climate change, economic developments and infrastructural development. With contributions from Sámi and non-Sámi scholars from Arctic regions, this book provides new insights into our understanding of the significance and legal protection of sacred sites for Sámi of the Arctic. It examines the role of international human rights, environmental law, and longstanding customary law that uphold Arctic indigenous peoples? rights in conservation, and their associated management systems. It also demonstrates the complex relationships between indigenous knowledge, cultural/spiritual values and belief systems and nature conservation. The book looks forward to providing guidelines for future research and practice for improved integration of the ethical, cultural and spiritual values of nature into law, policy, planning and management. As such, this book offers a contribution to upholding the sanctity of these sites, their cultural identity and the biodiversity associated with them.
Keywords: Sami (European people) -- Homes and haunts.; Indigenous peoples -- Homes and haunts -- Arctic regions.; Sami (European people) -- Religion.; Indigenous peoples -- Arctic regions -- Religion.; Sami (European people) -- Legal status, laws, etc.; Indigenous peoples -- Legal status, laws, etc. -- Arctic regions.; Sacred space -- Law and legislation -- Arctic regions.; Customary law -- Arctic regions.; Arctic Regions.; elektronické knihy; electronic books